Elements of News Literacy: A Focus Group Study of How Teenagers Define News and Why They Consume It. (September 2016) - Craft, Stephanie; Ashley, Seth; Maksl, Adam
Focus groups with teenagers (ages 15–18) were conducted to understand how they define news; what motivates them to consume news; what news sources they use; and how much knowledge about the news media industry, content, and effects they bring to the task of consuming and thinking critically about the news. Findings suggested exposure to news came largely incidentally via social media and/or parents; participants expressed the sense that news would find them. These teens saw news as depressing, conflict-ridden, and something that, although important, was of less value to them than to adults. Considered in light of a media literacy model adapted for news, these focus group participants exhibited a basic sense of news literacy but lacked the kind of knowledge about news industries, content, and effects that could better direct their own exposure, understanding, and subsequent civic engagement.